Presumption of Innocence : Evidential and Human Rights Perspectives. - Stumer, Andrew; Bell, John.; Kilpatrick, Claire (Oxford: Portland (Oregon): Hart, 2010)
This book investigates the supposed justifications for limitation of the presumption of innocence by analysing its history, rationale and scope.
Bibliograpy; index
Keywords: Comparative law; Human rights; Presumption of innocence -- Europe; Presumption of innocence -- Great Britain; Presumption of innocence; Human Rights; Droit compare; Droits de l'homme (Droit international); Presomption d'innocence -- Europe; Presomption d'innocence -- Grande-Bretagne.; Comparative law; Human rights; Presumption of innocence; Great Britain; Europe